The Linkage Between Human Trafficking and Migration: Identification of Victims - Ghazinyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2023)
Trafficking in human beings, as a modern form of slavery, severely violates people’s fundamental rights and dignity. The victims of human trafficking are being subjected to exploitation as a result of violence or the threat of it, fraud, or lack of awareness of their rights. Migrants are especially vulnerable to trafficking, and among them are especially those with certain socioeconomic issues or in need of international protection. Considering the socio-economic, humanitarian, and documentation problems of the aforementioned group and the probability of illegal movements and presence in the territory of certain countries, they are more vulnerable to trafficking. The current article seeks to analyze the correlation between migration and the phenomenon of human trafficking, as well as analyze the minimum necessary steps that the state authorities, particularly, those operating in the field of migration need to implement. Those activities should be aimed at ensuring effective combat against the trafficking in human beings by detecting and referring the relevant cases in the frame of migration to the competent authorities.